Liolamus espinozai (NCN): Predation - Robles, Cecilia Ines (2012)
Liolaemus espinozai has only been recently described and little is known about its natural history. It is found southeast of the Nevados del Aconquija in Catamarca province, Argentina, 2200–2800 m elev. (Abdala 2005. Rev. Esp. Herpetol. 19:5–17). It is a medium-sized lizard (approx. 60 mm SVL). The colubrid Philodryas psammophidea occurs within the distribution of L. espinozai and is known to feed on lizards (Scrocchi et al. 2006. Serpientes del Noroeste Argentino. Miscelanea, Fundación Miguel Lillo. 174 pp.). Here we report on an occurrence of predation by this snake on L. espinozai. On 18 February 2005, at ca. 1700 h, in Campo el Arenal, Catamarca (27.21°S, 66.23°W, datum WGS84; 2858 m elev.), an adult female L. espinozai was seen moving towards a shrub, perhaps responding to the presence of the observers. A Philodryas psammophidea happened to be in the aforementioned shrub. It immediately attacked the lizard, grasping it by the side of the body (Fig. 1). The lizard bit the snake on the side of its neck, a defensive response that might sometimes be effective as an antipredator mechanism (e.g., Leal and Rodríguez-Robles 1995. Copeia 1995:155–161). The snake slightly constricted the lizard, a technique many colubrids use to overcome larger prey (Zug 1993. Herpetology: An Introductory Biology of Amphibians and Reptiles. Academic Press, San Diego, California. 527 pp.). Later the snake located the lizard’s head and ingested it headfirst